A Satisfaction Study of Waterfront Public Spaces in Winter Cities from a Demand Perspective: A KANO-IPA Model Analysis Based on Northeastern China - Ping Yu; Yu Zhang (Land)
Urban waterfront public space is a key infrastructure for enhancing citizens’ well-being. However, rapid urbanization squeezes out blue and green spaces in cities, and extreme weather challenges exist in winter cities, resulting in unmet needs and a significant decline in citizens’ satisfaction. There is an urgent need to optimize design to bridge the gap between supply and demand. This study proposes a workflow for optimizing the design of waterfront spaces in winter cities based on the KANO-IPA model from the perspective of users’ demands. We constructed a systematic and comprehensive set of spatial demand indicators for waterfront public space in winter cities, covering seven demand dimensions and 42 indicators. A satisfaction survey was conducted across 12 sample reaches in northeastern China. We used the KANO model to classify the attributes of spatial demand indicators, then applied IPA analysis to evaluate them, and finally calculated priority indices to quantify their priority sequences. Based on this, we proposed three-phase optimization strategies: near-term priority upgrading, medium-term steady promotion, and far-term charm enhancement, offering recommendations for improving waterfront public spaces in winter cities. This study provides long-term support for urban regeneration, resource management, and waterfront public space design in winter cities.